Penerapan budidaya bandeng semi intensif dengan metode modular di tambak Universitas Muslim Indonesia, Kali Bone Kabupaten Pangkep - Jayadi Jayadi; Andi Asni; Ilmiah Ilmiah; Ida Rosada (DEDIKASI, 2019)
Innovation of semi-intensive milkfish cultivation and modular methods in the farming unit of the Indonesian Muslim University, Parreang Hamlet, Bontosunggu Village (Kalibone), Minasatene District, Pangkep Regency. The problem of demand for milkfish is the size of a lot of consumption, low production yields, traditional cultivation technology used, facilities and infrastructure are irrelevant, production management does not use good farming methods. The purpose of this activity is (1). applying the semi-intensive milkfish cultivation system technology innovation with a modular method, (2). Developing an economic culture, (3) creating new entrepreneurs of milkfish cultivation in ponds, (4) increasing milkfish production (4) stimulating the community to develop semi-intensive milkfish cultivation with a modular method, (5) stimulating students to innovate and develop milkfish farming. The implementation method is a demonstration of milkfish farming in ponds ranging from pond preparation, natural food growth, seed stocking, artificial feeding and probiotics, handling water quality, pests, and diseases, and harvesting. The density of seeds stocked with a semi-intensive system was 10,000 heads / ha. Map the ponds used for shifting maintenance (modular method) of 3 ponds for 5 months. The results achieved are the production of milkfish with size of 5 milkfish / kg or ± 250 g as much as 423 kg with a net income of Rp.4,390,000. The maintenance cycle is carried out one cycle because of the dry season constraints from the planned 3 maintenance cycles.